2016
DOI: 10.1016/j.actamat.2016.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Iterative thermomechanical processing of alloy 600 for improved resistance to corrosion and stress corrosion cracking

Abstract: The effects of thermomechanical processing (TMP) with iterative cycles of 10% cold work and strain annealing, on corrosion and stress corrosion cracking (SCC) behavior of alloy 600 was studied. The associated microstructural and cracking mechanisms were elucidated using transmission (TEM) and scanning electron microscopy (SEM), coupled with precession electron diffraction (PED) and electron back scatter diffraction (EBSD) mapping. TMP resulted in increased fraction of low coincident site lattice (CSL) grain bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 43 publications
3
26
0
1
Order By: Relevance
“…[4][5][6][7][8][9][10] GBE is the process of introducing a specific type and density of GBs through thermomechanical processing (TMP) to improve a GB-dependent property. Previous studies have shown GBE to be a successful method in mitigating intergranular stress corrosion cracking, 11,12 IGC, 5,13,14 hydrogen embrittlement, 15 and grain growth. 16 GBE is typically associated with the increase in specific coincidence site lattice (CSL) GBs, which have been considered special boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] GBE is the process of introducing a specific type and density of GBs through thermomechanical processing (TMP) to improve a GB-dependent property. Previous studies have shown GBE to be a successful method in mitigating intergranular stress corrosion cracking, 11,12 IGC, 5,13,14 hydrogen embrittlement, 15 and grain growth. 16 GBE is typically associated with the increase in specific coincidence site lattice (CSL) GBs, which have been considered special boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies on grain boundary engineering on Inconel 600 have also been tested with the DL−EPR. They have shown the improvement on Inconel 600 by thermo-mechanical treatments on the protection against intergranular corrosion [33][34][35]. In addition to the thermal treatments, mechanical processing such as cold work also use DL−EPR to assess the degree of sensitization of steels [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of resistance to intergranular failure of polycrystalline metallic materials has presented critical industry problems, such as intergranular corrosion (IGC) [1,2,3,4] and intergranular stress corrosion cracking (IGSCC) [5,6,7] as well as intergranular segregation/precipitation [8]. These problems are especially evident in austenitic stainless steels and Ni-based alloys exposed to light water reactor environments.…”
Section: Introductionmentioning
confidence: 99%
“…The synergistic effects of the corrosive condition and structural stress which are unavoidable due to the high temperature and high pressure water and the engineering structure caused these intergranular failures [9]. Grain boundary engineering (GBE) based on “grain boundary control and design”, which was first proposed by Watanabe in 1984 [10], has been demonstrated as a promising method to mitigate the intergranular degradation according to extensive investigations carried out in the last decades [1,2,3,4,5,6,7]. Instead of modifying the mechanics or chemistry [11], GBE provides a methodology to prevent intergranular degradation by control of the grain boundary (GB) network of materials, based on the idea that the percolation process of intergranular failure could be avoided if the proportion of corrosion-resistant boundaries was high enough in the GB network [1,12].…”
Section: Introductionmentioning
confidence: 99%